IMPLEMENTASI TEKNOLOGI DIGITAL MELALUI APLIKASI CANVA DALAM MENINGKATKAN MOTIVASI BELAJAR IPAS SISWA SDN 61 KARARA KOTA BIMA - Rosalina; Syarifuddin; Aris Iwansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The increasingly rapid development of information technology in the current era of globalization cannot be avoided anymore its influence on the world of education. Global demands require the world of education to always adapt technological developments of efforts to improve the quality of education. This study aims to determine the efferctiveness of the use of digital technology through the canva application in increasing the motivation to learn science in fifth grade students of SDN 61 Karara Bima City. This research is a classroom action research of the classroom assessment. The instruments used to collect data are observation sheets for the implementation of learning (teacher activities), observation sheets for student activities, student response questionnaires, and learning outcome tests in each cycle. The data obtained were analyzed using quantitative descriptive analysis is used to determine student learning outcomes while qualitative analysis is used to deremine the results od student activity observations. The results of the study showed that learning using digital technology based media through the canva application can increase the learning motivation of fifth grade students of state elementary school 61 Karara Bima City. This can be seen from the fifth grade students of state elementary school 61 Karara Bima City in cycle one of 63,64 % and in cycle two the average student leraning outcomes increased to 90,90 %. Students activity in the learning process also increased, although based on the students activity sheet in cycle one several obstacles were still felt cycle two showet significant improvement.